Response of corrugated interface on incident qSV-wave in monoclinic elastic half-spaces - Singh, Sanasam Sarat; Lalvohbika, J. (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with the problem of reflection and transmission of elastic waves due to an incident plane qSV-wave at a corrugated interface between two dissimilar monoclinic elastic half-spaces. Due to the corrugated nature of the interface, there exist regularly and irregularly reflected and transmitted elastic waves. Using Rayleigh's method of approximation, the reflection and transmission coefficients of regular and irregular waves are obtained for the first order of approximation. We have found that these coefficients are functions of the angle of incidence, elastic constants, corrugation and the frequency parameter.
Keywords: qSV and qP-waves; reflection coefficients; transmission coefficients; monoclinic medium; corrugated interface; phase velocity